A dual-function interleukin-1 receptor couples bacterial recognition to MyD88-dependent NF-κB activation during antibacterial immunity in shrimp - Siyou Huang; Wanli Lu; Yuxin Shi; Tao Lin; Xueer Tang; Song Guo; Xinhua Chen; Linwei Yang (Fish & Shellfish Immunology, 2026)

Injectable enzyme-triggered conductive hydrogel for restoring electrical homogeneity and functional recovery in myocardial infarction - Shun Xie; Fengjiao Deng; Ying Lu; Min Li; Shen Shen; Qin Wang; Weidong Li; Linwei Chen (Chemical Engineering Journal, 2026)

The membrane receptor Basigin facilitates WSSV infection by binding envelope proteins and suppressing antiviral gene expression in shrimp - Wanli Lu; Tongxin Lin; Mengting Luo; Yuxin Shi; Zhaohua Chen; Siyou Huang; Linwei Yang (Fish & Shellfish Immunology, 2026)

Early-Life Stages Amplify the Ecotoxicological Vulnerability of Freshwater Gastropods to the Agricultural Fungicide Prochloraz - Jiyuan Wang; Hairun Li; Jialu Xu; Yanlai Yao; Linwei Chen; Ruke Wang; Yuqing Shao; Lu Yang; Xiaofen Zhang; Xiaodong Yao; Lijun Lin; Hongyu Li (Journal of Hazardous Materials, 2026)

SAF-YOLO: Super-resolution augmented detection model with visual state space enhancement for safflower filament picking - Duan Mengyu; Wang Xiaorong; Qiu Linwei; Li Menghao; Chen Jinrong; He Liang (Precision Agriculture, 2026)

SFMT-Net: Underwater image enhancement framework with Multi-Scale spatial-Frequency matching transformation network - Boliang Guan; Guancheng Chen; Linwei Fan; Jintao Song; Xiaonan Luo (Ocean Engineering, 2026)

Salicylic acid-mediated biosynthesis of anti-oomycete diterpenoids in Euphorbia lathyris L. suspension cells - Pirui Li; Xi Sun; Guodong Zhang; Bi Wang; Chenxing Xiao; Mei Tian; Shu Xu; Hui Liu; Xu Feng; Linwei Li; Wanli Zhao; Yu Chen (Plant Cell Reports, 2026)

Identification and transcriptomic analysis of a new pathogen, Photobacterium damselae SCXP, associated with sea cucumber skin ulceration syndrome - Linwei Yang; Shuming Liu; Hui Lv; Haiyun Wei; Tong Wu; Bilian Lou; Jingsong Yang; Qingmei Huang; Yuxin Shi; Tongxin Lin; Zhengwei Cui; Xinhua Chen; et al. (Aquaculture, 2026)

Two key triggers and their mechanisms of the spring rainy season onset over southern China - Kexu Zhu; Wen Chen; Peng Hu; Linwei Jiang; Ruowen Yang; Lixuan Huang; Qingyu Cai; Yongmao Peng; Jingnan Li; Lu Gao; Qi Yan; Yehong Luo (Atmospheric Research, 2026)

Biodegradable polylactic acid (PLA) copolymer materials: Structural design, synthesis strategy, the relationship between structure and performance, industrial application - Rongrong Ji; Fan Mo; Linwei Liang; Chen Tian; Shixing Dong; Chang Deng; Hao Wu; Ling Zhou; Xipo Zhao (Chemical Engineering Journal, 2025)

Biobased carbon quantum dots: An emerging nano-enabled paradigm for pesticide removal and sustainable plant protection - Usman Arshad; Dan Chen; Haichao Cao; Chao Feng; Linwei Liu; Muhammad Amjad Ali; Zhang Wanhong; Yishan Li; Lijun Jiang; Jinguang Yang (Science of The Total Environment, 2025)

A novel LRR domain-containing C-type lectin gene with immune regulatory functions protects Penaeus vannamei against Vibrio parahaemolyticus infection - Kejia Weng; Ruoyu Liu; Chengqi Xiong; Yuxin Shi; Wenqian Chen; Chuanqi Wang; Linwei Yang (Fish & Shellfish Immunology, 2025)

Identification of the exposure pathway to micro-scaled biogenic silica debris via diet and its potential effect in promoting esophageal squamous cell carcinoma - Shenxi Deng; Yi Yang; Erica Celeste Conway; Si Li; Cha Huang; Zigu Chen; Haisheng Wu; Yuan He; Shuzhe Xie; Aifang Ji; Jingyan Zhang; Yansheng Gu; et al. (Journal of Hazardous Materials, 2025)

Synergistic treatment of respiratory syncytial virus induced pneumonia by multifunctional Baicalin-Resveratrol self-assembled nanomedicine - Chenqi Chang; Yu Zheng; Chang Lu; Ying Ma; Liang Wu; Yunyu Zhang; Lili Lin; Liang Guo; XiuZhen Chen; Linwei Chen; Jianming Cheng; Rui Chen (Chemical Engineering Journal, 2025)

7-Hydroxylathyrol defeats geminivirus through targeting C4 and activating host defense - Bi Wang; Xiaoxiao Xu; Wenhao Liang; Tong Shi; Qizhi Wang; Yu Chen; Sha Chen; Fei Liu; Linwei Li (Pesticide Biochemistry and Physiology, 2025)

Improvement of soil quality, microbial community structure and function with the application of microbial agent in continuous cropping of Pinellia ternata - Rong Deng; Yuan Zhao; Lin Chen; Siqi Li; Linwei Jiang; Xiaomei Wang; Tao Yang; Xueping Tian; Jun Huang (Plant and Soil, 2025)

Observational climatology and interannual variability of the spring rainy season onset over southern China: Objective definition and influence from tropical Pacific Ocean - Kexu Zhu; Wen Chen; Peng Hu; Yehong Luo; Ruowen Yang; Linwei Jiang; Qingyu Cai; Lu Gao; Jingnan Li; Yongmao Peng; Changhao Wu; Ziqi Niu (Atmospheric Research, 2025)

Establishment of virus-induced gene silencing in Euphorbia lathyris L. and its application in casbene synthase (CBS) gene functional analysis - Wei Lyu; Mei Tian; Long Huang; Bi Wang; Pirui Li; Wanli Zhao; Linwei Li; Xu Feng; Shu Xu; Yu Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

A reversible solar photothermal Li-CO2 battery enabled by engineering 3D plasmonic Cr-N-Ru catalysts assembled on carbon-free Si NP cathode - Shimin Chen; Junnan Han; Zhihuan Li; Zijie Lin; Min Wang; Hucheng Song; Xiaodong Pi; Dongke Li; Linwei Yu; Jun Xu; Kunji Chen (Chemical Engineering Journal, 2025)

In vitro simulated digestive properties of Monascus vinegar melanoidins, and cytoprotective functions on Caco-2 cells - Kuaitian Wang; Yuwei Li; Xiaojia Bian; Chen Wang; Donghui Geng; Linwei Yu; Yongqiang Cheng; Hongbin Chen; Ning Tang (Food Research International, 2025)

The Distribution Characteristics and Influencing Factors of the CO2 Fluxes Across the Sea–Air Interface in the Artificial Reefs Area of Sanheng Island - Mingdong Zhu; Kai Wang; Xu Zhao; Linwei Dai; Lei Chen; Hanyu Zhou (Journal of Marine Science and Engineering, 2024)
In order to study the impact of artificial reef construction on marine carbon sinks, a one-year monitoring and analysis were carried out in the Sanheng artificial reef areas of Shengsi Island. The main parameters observed were sea surface temperature, salinity, pH, total alkalinity (TA), and dissolved inorganic carbon (DIC). The partial pressure of CO2 (pCO2w) in the surface water and the CO2 flux (FCO2) across the sea–air interface were calculated and analyzed. The results showed that the annual range of surface water pCO2w was 34.48~501.53 μatm, and the partial pressure of CO2 decreases in the following order: winter, spring, autumn, summer. The FCO2 was significantly negatively correlated with temperature and significantly positively correlated with salinity and TA. The FCO2 in the four seasons decreases in the following order: winter, spring, autumn, summer. The annual sea–air flux in the survey area ranged from −108.79 to 41.74 mmol m−2 d−1. In winter, both the reef area and the control area displayed positive FCO2 values, indicating a source of CO2, while in the other three seasons, CO2 flux values were negative, indicating an overall CO2 sink. Additionally, in autumn, the reef area exhibited a stronger CO2 sink than the control area. The results indicated that the construction of artificial reefs has a certain carbon sink effect, with no significant difference in effectiveness between different artificial reef construction models.

Lignocellulose degradation and temperature adaptation mechanisms during composting of mushroom residue and wood chips at low temperature with inoculation of psychrotolerant microbial agent - Xueping Tian; Xiaomeng Qin; Xiaojun Jia; Qingyang Lyu; Siqi Li; Linwei Jiang; Lin Chen; Zhiying Yan; Jun Huang (Environmental Pollution, 2024)

Baseline sensitivity and resistance risk of Sclerotinia sclerotiorum to glabridin and the possible anti-fungal mechanism - Shu Xu; Chenyang Liu; Jin Chen; Linwei Li; Siwei Qiao; Mei Tian; Qian Zhou; Xingzeng Zhao; Yu Chen; Fei Liu; Xu Feng (Pesticide Biochemistry and Physiology, 2024)

Discovery of ElABCG39: a key player in ingenol transmembrane efflux identified through genome-wide analysis of ABC transporters in Euphorbia lathyris L. - Guyin Lin; Pirui Li; Linwei Li; Ruyuan Wang; Wanli Zhao; Mei Tian; Junzhi Wu; Shu Xu; Yu Chen; Xu Feng (Plant Cell Reports, 2024)

Targeted discovery of unusual diterpenoids with anti-fungal activity from the root of Euphorbia lathyris - Yiwei Wang; Shu Xu; Guodong Zhang; Pirui Li; Chenyang Liu; Jiarui Zhou; Xu Feng; Linwei Li; Yu Chen (Phytochemistry, 2024)

A novel anti-angiogenesis peptide in combination with cisplatin self-assembling into tube-like nanomedicine for oral treatment of gastric cancer - Linwei Chen; Qin Wang; Yong Jiang; Liu Xu; Nina Wei; Chang Lu; Chenqi Chang; Dandan Song; Yutong Wang; Li Wu; Weidong Li; Xiaobin Jia; et al. (Chemical Engineering Journal, 2024)

Myosin Va-dependent Transport of NMDA Receptors in Hippocampal Neurons - Ru Gong; Linwei Qin; Linlin Chen; Ning Wang; Yifei Bao; Wei Lu (Neuroscience Bulletin, 2024)
N-methyl-D-aspartate receptor (NMDAR) trafficking is a key process in the regulation of synaptic efficacy and brain function. However, the molecular mechanism underlying the surface transport of NMDARs is largely unknown. Here we identified myosin Va (MyoVa) as the specific motor protein that traffics NMDARs in hippocampal neurons. We found that MyoVa associates with NMDARs through its cargo binding domain. This association was increased during NMDAR surface transport. Knockdown of MyoVa suppressed NMDAR transport. We further demonstrated that Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) regulates NMDAR transport through its direct interaction with MyoVa. Furthermore, MyoVa employed Rab11 family-interacting protein 3 (Rab11/FIP3) as the adaptor proteins to couple themselves with NMDARs during their transport. Accordingly, the knockdown of FIP3 impairs hippocampal memory. Together, we conclude that in hippocampal neurons, MyoVa conducts active transport of NMDARs in a CaMKII-dependent manner.

Structural effects of sulfonamides on the proliferation dynamics of sulfonamide resistance genes in the sequencing batch reactors and the mechanism - Ligui Wu; Mingyu Wang; Lingling Rong; Wenbiao Wang; Linwei Chen; Qiaofeng Wu; Haoyu Sun; Xiangfeng Huang; Xiaoming Zou (Journal of Environmental Sciences, 2024)

Unveiling changes in the complexation of dissolved organic matter with Pb(II) by photochemical and microbial degradation using fluorescence EEMs-PARAFAC - Liyang Yang; Linwei Chen; Wan-E Zhuang; Zhuoyi Zhu (Environmental Pollution, 2024)

Automatic identification of illegal construction and demolition waste landfills: A computer vision approach - Qiaoqiao Yong; Huanyu Wu; Jiayuan Wang; Run Chen; Bo Yu; Jian Zuo; Linwei Du (Waste Management, 2023)

A large-scale climate-aware satellite image dataset for domain adaptive land-cover semantic segmentation - Songlin Liu; Linwei Chen; Li Zhang; Jun Hu; Ying Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

On vibration isolation performance and crashworthiness of a three-dimensional lattice metamaterial - Linwei Zhang; Zhonghao Bai; Qiang Zhang; Yao Jin; Yafeng Chen (Engineering Structures, 2023)

The Hippo-Yki pathway downstream transcription factor Scalloped negatively regulates immune defense against Vibrio parahaemolyticus infection in shrimp - Linwei Yang; Deyu Han; Zi-ang Wang; Nuo Chen; Hongliang Zuo; Zhixun Guo; Menghuang Xu; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2023)

Current investigation status of oxy-fuel circulating fluidized bed combustion - Ge Chen; Li Shiyuan; Wang Linwei (Fuel, 2023)

Fluoxetine alleviates postoperative cognitive dysfunction by attenuating TLR4/MyD88/NF-κB signaling pathway activation in aged mice - Yusheng Yao; Daoyi Lin; Yuzhi Chen; Linwei Liu; Yushang Wu; Xiaochun Zheng (Inflammation Research, 2023)

A novel Toll receptor from Pacific white shrimp Penaeus vannamei is involved in immune defense against Vibrio parahaemolyticus infection - Shengwen Niu; Yuening Zhu; Ran Geng; Nuo Chen; Mengting Luo; Hongliang Zuo; Linwei Yang; Shaoping Weng; Jianguo He; Xiaopeng Xu (Aquaculture, 2023)

Enhancement in the thermoelectric performance of ZrNiSn-based alloys through extra Zr-rich nanoprecipitates with superstructures - Ruonan Min; Yinlu Gao; Xue Jiang; Xiong Yang; Linwei Li; Huijun Kang; Enyu Guo; Zongning Chen; Tongmin Wang (Chemical Engineering Journal, 2023)

Effect of antifreeze protein on the quality and microstructure of frozen chicken breasts - Junlin Chen; Yaqi Fan; Xingguo Zhang; Zimeng Yuan; Hairu Zhang; Xinglian Xu; Jun Qi; Guoyuan Xiong; Lin Mei; Yuan Zhu; Linwei Yang; Chao Li (Food Chemistry, 2023)

Subsurface oxygen minima regulated by remineralization and bottom flushing along 123°E in the inner East China Sea - Bin Wang; Jianfang Chen; Haiyan Jin; Dewang Li; Shengquan Gao; Shichao Tian; Lin Sun; Haizhou Zhang; Linwei Li (Frontiers in Marine Science, 2023)
The summer hypoxia off the Changjiang Estuary is one of the largest coastal hypoxic systems in the world and has displayed spatial heterogeneity in recent years. Based on observation data in the summer of 2014, hypoxia was identified both in the bottom and mid-layers. Except for the typical bottom hypoxia in the submarine canyon, the subsurface oxygen minima (SOM) were captured in the mid-layer of 10~15 m, with lower dissolved oxygen in the mid-layer than at the bottom (30–50 m). This SOM phenomenon was located in the lower boundary of the pycnocline and above the Taiwan warm current (TWC) and Kuroshio subsurface water (KSSW). Due to the southern expansion of Changjiang diluted water (CDW), a high phytoplankton biomass (the maximum chlorophyll a of 25 μg L −1 , pH of 8.6, and DO of 11 mg L −1 ) band occupied the surface area along 123°E. By analyzing the 24-h continuous observation and high-resolution profile data, we revealed that the subsurface oxygen minima were predominantly controlled by remineralization and bottom-flushing effects. Fast local consumption occurred near the pycnocline layer, while the lateral transport of oxygen-rich ambient water replenished the bottom oxygen deficit from south to north. We summarize and contextualize three hot spots of hypoxia into a conceptual diagram and emphasize the influences of advection, mixing, and respiration on their location and severity. Overall, compared with the discussion about the low DO background of TWC/KSSW, this research highlights the flushing effects of TWC/KSSW that will reshape the hypoxia structure and alleviate the hypoxia severity in the south hypoxia area off the Changjiang Estuary.

Structural control on the Baiyinha'er gold mineralization (Southern Central Asian Orogenic belt) related to Early Paleozoic Paleo-Asian Oceanic subduction - Junlai Liu; Tao Jin; Yangwang Ou; Linwei Li; Cheng Zhang; Tianjiao Lu; Xiaoyu Chen (International Journal of Earth Sciences, 2022)

Alkalinity export to the ocean is a major carbon sequestration mechanism in a macrotidal saltmarsh - Yvonne Y.Y. Yau; Pei Xin; Xiaogang Chen; Lucheng Zhan; Mitchell Call; Stephen R. Conrad; Christian J. Sanders; Linwei Li; Jinzhou Du; Isaac R. Santos (Limnology and Oceanography, 2022)
Saltmarshes are a blue carbon ecosystem accumulating large quantities of organic carbon in sediments. Some of this carbon can be transformed into dissolved inorganic carbon (DIC) and methane (CH 4 ) that may eventually be exported to the ocean or atmosphere. Although extensive studies have quantified specific components of the carbon budget such as carbon burial, limited attention has been given to pore‐water‐derived carbon and total alkalinity (TA) exports to the ocean. Here, we quantified lateral exports to the ocean (outwelling) of 202 ± 160 and 78 ± 75 mmol m −2 d −1 of DIC and TA, respectively. The TA : DIC concentration ratio in the creek waters was ~ 1, implying TA production from anaerobic mineralization in sediments. The lateral TA exports were comparable to the local (94 ± 48 mmol m −2 d −1 ) and national (~ 50 mmol m −2 d −1 ) organic carbon burial. High TA exports could locally increase the ocean buffering capacity and contribute bicarbonate to the coastal ocean, acting as a long‐term carbon storage. Pore water traced by radon contributed 28–37% and 58–69% of DIC and TA exports. Separating the two major DIC components (i.e., CO 2 emissions and alkalinity exports) is essential to resolve the carbon sequestration potential from saltmarshes. Here, dissolved CO 2 emissions to the atmosphere accounted for 3–5% of total DIC outwelling. CH 4 emissions played a minor role offsetting around 0.3 to 6% of the carbon sequestration. Overall, we demonstrate that alkalinity export into the ocean can be an overlooked carbon sequestration pathway in saltmarshes at rates comparable to carbon burial.

Reverse-Time Migration of Converted S-Waves of Varying Densities - Siyou Tong; Ming Chen; Huawei Zhou; Linwei Li; Xiugang Xu; Zhiqiang Wu (Journal of Ocean University of China, 2019)

Bituminous coal combustion and Xuan Wei Lung cancer: a review of the epidemiology, intervention, carcinogens, and carcinogenesis - Jinhui Li; Jinjun Ran; Lung-chi Chen; Max Costa; Yunchao Huang; Xiao Chen; Linwei Tian (Archives of Toxicology, 2019)

Expanding indole diversity: direct 1-step synthesis of 1,2-fused indoles and spiroindolines from 2-halo anilines for fast SAR antiviral elucidation against tobacco mosaic virus (TMV) - Linwei Chen; Yongxian Liu; Hongjian Song; Yuxiu Liu; Lizhong Wang; Qingmin Wang (Molecular Diversity, 2017)

Overexpression of the iron transporter NtPIC1 in tobacco mediates tolerance to cadmium - Xun Gong; Linwei Yin; Jiaqi Chen; Changhong Guo (Plant Cell Reports, 2015)